1999
DOI: 10.7164/antibiotics.52.474
|View full text |Cite
|
Sign up to set email alerts
|

Sanglifehrins A, B, C and D, Novel Cyclophilin-binding Compounds Isolated from Streptomyces sp. A92-308110. II. Structure Elucidation, Stereochemistry and Physico-chemical Properties.

Abstract: A novel class of macrolides, the sanglifehrins, was discovered by screening of actinomycete strains with a cyclophilin-binding assay. The chemical structures and absolute stereochemistries of the sanglifehrins A, B, C and D were determined unambiguously by NMR-techniques and by X-ray crystallography of the complex with cyclophilin A.Sanglifehrin A consists of a 22-membered macrocycle containing a tripeptide subunit and features in position 23 a chain of nine carbon atoms bearing a spirocyclic substituent. Sang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
73
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 0 publications
2
73
0
Order By: Relevance
“…S anglifehrins, described originally by Sanglier et al (1,2), are novel immunophilin-binding immunosuppressants with an unknown mechanism of action that are produced by the actinomycetes strain Streptomyces A92-308110. The immunophilin-binding agent cyclosporin A (CsA) 3 binds to cyclophilin and inhibits activity of the calcineurin phosphatase, whereas both FK506 and rapamycin (Rapa) bind to the FK506 binding protein but inhibit two different effector proteins: calcineurin phosphatase and mammalian target of Rapa (mTOR), respectively (3,4).…”
mentioning
confidence: 99%
“…S anglifehrins, described originally by Sanglier et al (1,2), are novel immunophilin-binding immunosuppressants with an unknown mechanism of action that are produced by the actinomycetes strain Streptomyces A92-308110. The immunophilin-binding agent cyclosporin A (CsA) 3 binds to cyclophilin and inhibits activity of the calcineurin phosphatase, whereas both FK506 and rapamycin (Rapa) bind to the FK506 binding protein but inhibit two different effector proteins: calcineurin phosphatase and mammalian target of Rapa (mTOR), respectively (3,4).…”
mentioning
confidence: 99%
“…These reports show that CypA might be important for tumorigenesis in solid tumors. CypA is also an immunophilin and a cytosolic receptor for the immunosuppressive drugs cyclosporin A (CsA) (5) and sanglifehrin A (SFA) (16). CsA binds to CypA, and this complex inhibits calcineurin, a calcium-dependent phosphatase, that regulates the expression of various cytokine genes ONCOLOGY REPORTS 23: 1053-1062, 2010 Cyclosporin A and sanglifehrin A enhance chemotherapeutic effect of cisplatin in C6 glioma cells (17).…”
Section: Introductionmentioning
confidence: 99%
“…Sanglifehrins represent novel immunophilin-binding agents, that exhibit >10 times higher binding affinity to the intracellular receptor of CsA, cyclophilin A, but unlike the latter, do not inhibit calcineurin phosphatase activity (7)(8)(9)(10)(11). SFA has an unique chemical structure consisting of a 22-membered macrocycle containing a tripeptide subunit and features in position 23 a chain of nine carbon atoms bearing a spirocyclic substituent (8).…”
Section: Introductionmentioning
confidence: 99%
“…SFA has an unique chemical structure consisting of a 22-membered macrocycle containing a tripeptide subunit and features in position 23 a chain of nine carbon atoms bearing a spirocyclic substituent (8). In vitro experiments revealed that sanglifehrin A (SFA) has no effects on targets of known immunosuppressants (9).…”
Section: Introductionmentioning
confidence: 99%